FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PREFERENSI KONSUMEN STREET FOOD PADA MAHASISWA UNIVERSITAS GADJAH MADA - , Endah Budi Permana P ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background : Habits and preference could influence the street food consumption. Consume food high fat, protein and carbohydrate could increase the risk suffered coronary heart, high blood pressure, diabetes mellitus and stroke. More than 90 % disease that occurs in human caused by food contamination microorganism (foodborne diseases) through among others, namely typhus, dicentry bacteria / amoeba, botulism and intoxication other bacteria, and hepatitis A. Objective : This study has purpose to analyze factors related to consumer preferences of street food at Universitas Gadjah Madaâs students. Method : Type of observational research with cross sectional design. Sample of research are 96 people undergraduates from class student 2012 in Universitas Gadjah Mada taken by cluster sampling. Data obtained by an interview using a questionnaire consumer preferences of street food, the individual and food characteristics. It through statistical analysis using correlation test (contingency coefficient and Spearman) and analysis multivariate use binominal the regression. Result : There is a correlation between sex (RR= 1,60